2004
DOI: 10.1002/macp.200400190
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Crystallization of Poly(ε‐caprolactone) in Blend with Poly(styrene‐co‐acrylonitrile): Influence of Phase Separation Process

Abstract: Summary: The isothermal crystallization process of poly(ε‐caprolactone) (PCL) and its blend with styrene‐acrylonitrile random copolymer containing 27.5 wt.‐% acrylonitrile has been investigated as a function of crystallization and melting temperatures for different melting times in the vicinity of the lowest critical solution temperature (LCST)‐type phase diagram using DSC. The obtained results showed that the isothermal crystallization kinetics from the melt of PCL in the blend was greatly affected by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 48 publications
6
28
0
Order By: Relevance
“…By using Equation (2), some characteristic kinetic parameters such as the half-life for crystallization (t 1/2 ), the bulk crystallization constant (k), and the Avramís exponent (n) were obtained. [30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…By using Equation (2), some characteristic kinetic parameters such as the half-life for crystallization (t 1/2 ), the bulk crystallization constant (k), and the Avramís exponent (n) were obtained. [30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…25 For PCL/SAN-30 blends at 100 8C, it is found that x is 8.95 for R974 and 1.30 for A200. [27][28][29] In addition, there is a temperature limit to observe the ring-banded pattern. And A200 mainly distribute alongside the interface of PCL phase and SAN phase.…”
Section: Phase Morphology Of Pcl/san/nanosilica Blendsmentioning
confidence: 99%
“…Thus, R974 should be preferentially located within PCL phase. 28 The isothermal crystalline morphology evolution of PCL/SAN-30/Nanosilica blends, with nanosilica concentration ranging from 0 to 4 wt % are investigated, as shown in Figures 6 and 7. Note that the blending conditions will also influence the distribution of nanosilica, so it is further verified by the TEM images [ Figure 4(a,b)].…”
Section: Phase Morphology Of Pcl/san/nanosilica Blendsmentioning
confidence: 99%
“…Crystallization kinetics of PCL/SAN blend was also studied [89]. The isothermal crystallization kinet ics of PCL in the blend was greatly affected by the presence of SAN, where the crystallization halftime (t 0.5 ) in the case of PCL/SAN (80/20) blend was much longer than corresponding value for pure PCL due to favorable interaction between of PCL and SAN.…”
Section: Polycaprolacton Systemsmentioning
confidence: 99%